2022
DOI: 10.1002/ajhb.23817
|View full text |Cite
|
Sign up to set email alerts
|

Age at menarche, environmental stress, and social inequality: Evidence from Poland in the 1930s–1950s

Abstract: Objective To address the relationship between socioeconomic factors and age of menarche among Polish women born and reared in periods that varied considerably in environmental stresses: the Great Depression of the 1930s, the interval of World War II, and the interval of communist rule following World War II through the 1950s. Methods The data set included information on age at menarche and socioeconomic status (SES) of 718 women born during the Great Depression (n = 182), WWII (n = 189), and post‐WWII through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Among Polish women, regular social gradients were found in most parameters of biological fitness. The different level of sensitivity of different social groups to the same external stimuli in the form of social and political changes in Poland has been confirmed by other analyses of the Polish population, such as the study of secular trends in the body height of children and adolescents or the maturation of girls [69,70]. They have indicated that certain social subgroups, such as those at the top of the social ladder, experience more dynamic changes in body height compared to lower subgroups.…”
Section: Psychosocial Stress and The Importance Of Socioeconomic Statusmentioning
confidence: 68%
“…Among Polish women, regular social gradients were found in most parameters of biological fitness. The different level of sensitivity of different social groups to the same external stimuli in the form of social and political changes in Poland has been confirmed by other analyses of the Polish population, such as the study of secular trends in the body height of children and adolescents or the maturation of girls [69,70]. They have indicated that certain social subgroups, such as those at the top of the social ladder, experience more dynamic changes in body height compared to lower subgroups.…”
Section: Psychosocial Stress and The Importance Of Socioeconomic Statusmentioning
confidence: 68%